THE ROLE OF ISLAMIC EDUCATION MANAGEMENT IN SHAPING THE ISLAMIC IDENTITY OF INDONESIAN YOUTH - Ahmad Zainuri (STIT Pringsewu, 2025)
This study examines the vital role of Islamic education management in shaping the identity of youth in Indonesia, the world's largest Muslim-majority nation. Using a qualitative approach and a literature review method, the research analyzes academic literature to identify key themes related to educational management, such as leadership, curriculum, and teacher management. The findings indicate that effective management significantly influences the strengthening of religious commitment, the formation of moral values, and the resilience of youth against the influences of globalization and digital media. However, challenges such as a lack of teacher training and policy gaps persist. This research recommends the need for strategic adaptation in management practices, stronger policy support, and further empirical research to ensure Islamic education remains relevant and effective in guiding Indonesia's golden generation.